Raptor/mTORC1 Acts as a Modulatory Center to Regulate Anti-bacterial Immune Response in Rockfish - Li, Kang; Wei, Xiumei; Zhang, Libin; Chi, Heng; Yang, Jialong (Frontiers in Immunology, 2019)
The mammalian target of rapamycin (mTOR) is an evolutionarily highly conserved atypical serine/threonine protein kinase, which regulates cell growth, proliferation, apoptosis, autophagy and metabolism. As a regulatory protein, Raptor is awfully important for the stability and function of mTOR complex 1 (mTORC1). However, the studies about how Raptor/mTORC1 participates in and regulates immune response in lower vertebrates are still limited. In this study, we investigated the regulation of immune response by the Raptor/mTORC1 signaling pathway in rockfish Sebastes schlegelii. S. schlegelii Raptor (Ss-Raptor) is a highly conserved protein during the evolution, in both primary and tertiary structure. Ss-Raptor mRNA was widely distributed in various tissues of rockfish and has a relative higher expression in spleen and blood. After infected by Micrococcus luteus or Listonella anguillarum, mRNA expression of Ss-Raptor rapidly increased within 48 hours. Once Raptor/mTORC1 signaling was blocked by rapamycin, expression of the pro-inflammatory cytokines IL-1β and IL-8 was severely impaired, suggesting potential regulatory role of Raptor/mTORC1 signaling in the innate immune response of rockfish. In addition, Raptor/mTORC1 pathway participated in lymphocyte activation of rockfish through promoting 4EBP1 and S6 phosphorylation. Inhibition of Raptor/mTORC1 signaling crippled the lymphocyte expansion during primary adaptive immune response, manifesting by the decrease of lymphoid organ weight and lymphocyte numbers. More importantly, inhibition of Raptor/mTORC1 signaling impaired the lymphocyte mediated cytotoxic response, and made the fish more vulnerable to the bacterial infection. Together, our results suggested that Raptor and its tightly regulated mTORC1 signaling acts as modulatory center to regulate both innate and lymphocyte-mediated adaptive immune response during bacterial infection. This research has shed new light on regulatory mechanism of teleost immune response, and provide helpful evidences to understand the evolution of immune system.